Solar-Powered Electrocoagulation System for Tofu Wastewater Treatment and its Characteristic - Muryanto Muryanto; Ajeng Arum Sari; Sunu Pertiwi; Danar Aji Prasetyo; Sudarno Sudarno (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
This study aims to investigate the ability of solar-powered electrocoagulation for tofu wastewater, especially for reducing COD and TSS. This feasibility was compared with conventional electrocoagulation using electricity from the state electricity company. The study was conducted on a laboratory scale using a batch reactor electrocoagulation and aluminium electrode. The types of electrolytes used are sodium chloride and potassium chloride. The contact time is 0, 2, 4, 6, and 8 hours. The results showed that removal of COD and TSS in tofu wastewater increases with a longer electrolysis time. During two hours of electrolysis time, the removal of COD and TSS were 25 and 53.85%, respectively. This process yielded the highest COD and TSS removal of 75 and 76.9%, respectively, at 6 hours. Pseudo-second order kinetics about COD removal, both in conventional and solar panel systems, is concluded. By adding NaCl electrolytes, the conductivity of wastewater was increased, and then the removal of COD and TSS was also increased. At the end of the electrolysis time (5 hours), the pH of wastewater was neutral. The results of sludge characterization using FTIR showed the presence of hydroxyl groups, amide compound, and aromatic compound.  The process of using solar panels gives results slightly different from conventional electricity, but has advantages in terms of lower operating costs and environmental friendly.